18.7k views
3 votes
Can u help me with this please .

Can u help me with this please .-example-1
User Sifoo
by
4.6k points

2 Answers

5 votes

Answer:

x³ + 6x² + 8x

Explanation:

Given

x(x + 2)(x + 4)

Begin by expanding the pair (x + 2)(x + 4)

Each term in the second factor is multiplied by each term in the first factor, that is

x(x + 4) + 2(x + 4) ← distribute both parenthesis

= x² + 4x + 2x + 8 ← collect like terms

= x² + 6x + 8

Now multiply this by x, that is

x(x² + 6x + 8) ← distribute parenthesis

= x³ + 6x² + 8x

Hence

x(x + 2)(x + 4) = x³ + 6x² + 8x

User Yvan
by
4.3k points
6 votes

Answer:

x³ + 6x² + 8x

Explanation:

x(x+2)(x+4) (expand the expressions in parentheses by polynomial product distribution)

= x [(x)(x) + (x)(4) + (2)(x) + (2)(4)]

= x (x² + 4x + 2x + 8)

= x (x² + 6x + 8) multiply & distribute the x term into the parentheses

= x² (x) + 6x(x) + 8(x)

= x³ + 6x² + 8x

User Robru
by
5.2k points